A Simple Clinical Risk Score (C 2 HEST) for Predicting Incident Atrial Fibrillation in Asian Subjects: Derivation in 471,446 Chinese Subjects, With Internal Validation and External Application in 451,199 Korean Subjects - Li, Yan-Guang; Pastori, Daniele; Farcomeni, Alessio; Yang, Pil-Sung; Jang, Eunsun; Joung, Boyoung; Wang, Yu-Tang; Guo, Yu-Tao; Lip, Gregory Y H (Chest, 2019)
The incidence of atrial fibrillation (AF) is increasing, conferring a major health-care issue in Asia. No risk score for predicting incident AF has been specifically developed in Asian subjects. Our aim was to investigate risk factors for incident AF in Asian subjects and to combine them into a simple clinical risk score. Risk factors for incident AF were analyzed in 471,446 subjects from the Chinese Yunnan Insurance Database (internal derivation cohort) and then combined into a simple clinical risk score. External application of the new score was performed in 451,199 subjects from the Korean National Health Insurance Service (external cohort). In the internal cohort, structural heart disease (SHD), heart failure (HF), age ≥ 75 years, coronary artery disease (CAD), hyperthyroidism, COPD, and hypertension were associated with incident AF. Given the low prevalence and the strong association of SHD with incident AF (hazard ratio, 26.07; 95% CI, 18.22-37.30; P < .001), these patients should be independently considered as high risk for AF and were excluded from the analysis. The remaining predictors were combined into the new simple C HEST score: C : CAD/COPD (1 point each); H: hypertension (1 point); E: elderly (age ≥ 75 years, 2 points); S: systolic HF (2 points); and T: thyroid disease (hyperthyroidism, 1 point). The C HEST score showed good discrimination with the area under the curve (AUC) of 0.75 (95% CI, 0.73-0.77) and had good calibration (P = .774). The score was internally validated by bootstrap sampling procedure, giving an AUC of 0.75 (95% CI, 0.73-0.77). External application gave an AUC of 0.65 (95% CI, 0.65-0.66). The C HEST score was superior to CHADS and CHA DS -VASc scores in both cohorts in predicting incident AF. We have developed and validated the C HEST score as a simple clinical tool to assess the individual risk of developing AF in the Asian population without SHD.